2020
DOI: 10.1021/acs.jpcc.9b10923
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Adsorption of Lysozyme on Nanodiamonds in Aqueous Suspensions

Abstract: The interactions of one of the most famous enzymes, lysozyme, with carboxylated nanodiamonds in water were studied. It was found that stable complexes are formed as a result of lysozyme adsorption on the surface of nanodiamonds. Based on the obtained adsorption isotherms and change in the fluorescence of nanodiamonds during the adsorption of lysozyme on them, it is concluded that lysozyme is adsorbed on carboxylated nanodiamonds in two layers. Numerical estimates and IR absorption spectroscopy data showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…Properties of CNPs are largely defined by the processes occurring at the interface between nanoparticles and their environment. Like that, for both nanodiamonds (NDs) and carbon dots (CDs), the structure of surface groups and peculiarities of their interactions with surrounding molecules influence the colloidal stability of nanoparticles and their adsorption properties and biocompatibility. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Properties of CNPs are largely defined by the processes occurring at the interface between nanoparticles and their environment. Like that, for both nanodiamonds (NDs) and carbon dots (CDs), the structure of surface groups and peculiarities of their interactions with surrounding molecules influence the colloidal stability of nanoparticles and their adsorption properties and biocompatibility. …”
Section: Introductionmentioning
confidence: 99%
“…Photoluminescence (PL) of NDs and CDs is also dependent on the properties of nanoparticles’ surfaces and their immediate environment. For NDs, the depednece of PL on their surface chemistry, on the strength of the environments’ hydrogen bonds, ,, and on interactions with biomolecules , allowed us to distinguish the specific type of ND emission:surface photoluminescence, distinct from the well-studied PL of color centers in the diamond core. Recently, increasingly more authors believe that the source of surface PL of nanodiamonds is the functionalized sp 2 -hybridized carbon on their surfaces. …”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] In the multilayer form, each layer of lysozyme possesses a different structural conformation and orientation, i.e., the first layer adsorbs with side-on orientation with more conformational change compared to the second layer having end-on orientation. 25 It is reported that a monolayer of lysozyme (side-on) has been adsorbed on a hydrophilic surface while a bi-or tri-layer has been deposited on a hydrophobic surface. 26 Lower adsorption of lysozyme on hydrophilic (negatively charged) silica surfaces was recorded with increasing ionic strength of monovalent Na + ions, because of ionic screening between the protein and silica surface.…”
Section: Introductionmentioning
confidence: 99%
“…27–29 Surface functionalization with carboxylic groups offers greater colloidal stability of ND when dispersed in polar solvents 30–32 as well as their enhanced biocompatibility, which is of great importance for their biomedical applications. 33…”
Section: Introductionmentioning
confidence: 99%